Molnupiravir promotes SARS-CoV-2 mutagenesis via the RNA template - Gordon, Calvin J.; Tchesnokov, Egor P.; Schinazi, Raymond F.; Götte, Matthias (The Journal of biological chemistry, 2021)
The RNA-dependent RNA polymerase of the severe acute respiratory syndrome coronavirus 2 is an important target in current drug development efforts for the treatment of coronavirus disease 2019. Molnupiravir is a broad-spectrum antiviral that is an orally bioavailable prodrug of the nucleoside analogue β-D-N4-hydroxycytidine (NHC). Molnupiravir or NHC can increase G to A and C to U transition mutations in replicating coronaviruses. These increases in mutation frequencies can be linked to increases in antiviral effects; however, biochemical data of molnupiravir-induced mutagenesis have not been reported. Here we studied the effects of the active compound NHC 5’-triphosphate (NHC-TP) against the purified severe acute respiratory syndrome coronavirus 2 RNA-dependent RNA polymerase complex. The efficiency of incorporation of natural nucleotides over the efficiency of incorporation of NHC-TP into model RNA substrates followed the order GTP (12,841) > ATP (424) > UTP (171) > CTP (30), indicating that NHC-TP competes predominantly with CTP for incorporation. No significant inhibition of RNA synthesis was noted as a result of the incorporated monophosphate in the RNA primer strand. When embedded in the template strand, NHC-monophosphate supported the formation of both NHC:G and NHC:A base pairs with similar efficiencies. The extension of the NHC:G product was modestly inhibited, but higher nucleotide concentrations could overcome this blockage. In contrast, the NHC:A base pair led to the observed G to A (G:NHC:A) or C to U (C:G:NHC:A:U) mutations. Together, these biochemical data support a mechanism of action of molnupiravir that is primarily based on RNA mutagenesis mediated via the template strand.